KECERDASAN EMOSIONAL DAN PENCAPAIAN PRESTASI AKADEMIK MAHASISWA DI JURUSAN AKUNTANSI POLITEKNIK NEGERI SRIWIJAYA - Maria, Maria (Universitas PGRI Palembang, 2012)
ABSTRACTThis research aims to measure the effect of Emotional Quotient (EQ) toward the attainment ofacademic achievement at accounting department Polsri both simultaneously and partially. Itscontribution would have been expected to ideas towards the importance of emotional intelligence inthe world of student academic achievement and preparation to enter the workforce later. In addition,the expediency of emotional intelligence will contribute to the learning process of accounting that hasa comprehensive strategy encompassing skills/expertise, knowledge, and professional orientation.The data has been gathered by sampling to student at accounting department Polsri. The researchsamples are 344 respondents selected by stratified random. This type of research is descriptiveverifikatif.The result indicated that self awareness, self regulation, motivation, empathy and social skillhave influences toward the attainment of academic achievement both simultaneously and partially.Entirely, the result identified about the self awareness, self regulation, motivation, empathy and socialskill have significantly effects to academic achievement at accounting department PolsriKey words: emotional quotient, academic achievement